Ruang Keagamaan Digital: Persepsi Pengguna TikTok dan Youtube terhadap Konten Gus Baha - Pamungkas, Jati; Azis Prastica; Imam Sholikhuddin (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The phenomenon of digital da'wah has significantly transformed the ways religious knowledge is accessed, interpreted, and disseminated in contemporary society. This study aims to analyze the patterns of actions and perceptions of TikTok and YouTube users toward religious content delivered by Gus Baha within the context of the digital religious space. Using Max Weber’s theory of rationalization as an analytical framework, this research explores how religious authority, knowledge transmission, and user interpretation undergo processes of rationalization on digital platforms.This study employs a qualitative approach using virtual ethnography, content analysis, and in-depth interviews with users of both platforms. Data were collected through observation of uploaded content, analysis of user interactions and comments, and examination of engagement dynamics.The findings indicate that user responses to Gus Baha’s content reflect Weber’s four types of social action. Instrumentally rational actions are evident in the use of short videos as practical and efficient learning tools. Value-oriented rational actions appear in users’ consistent efforts to deepen religious understanding. Affective actions emerge from emotional attachment to Gus Baha’s communicative style, while traditional actions are reflected in the perception of digital da'wah as a continuation of established religious learning traditions. Furthermore, digital rationalization through algorithms, short-video formats, and platform accessibility, shapes how religious knowledge is selected, interpreted, and circulated.This study concludes that digital religious spaces function not only as channels of dissemination but also as arenas for the transformation of religious authority, meaning construction, and religious practice in the digital era.